Perhitungan Cost of Treatment pada Pasien Rawat Inap Penderita Stroke Peserta BPJS di RSUD dr. Mohamad Saleh Kota Probolinggo - Munawwarah, Azizah (Jurnal Ekonomi Kesehatan Indonesia, 2021)
Stroke is one of the catastrophic diseases which is the most cause of death in Indonesia. Probolinggo is the second highest prevalence city of stroke in East Java. The prevalence and mortality of stroke have increased in RSUD dr. Mohamad Saleh Probolinggo. Stroke is a high-cost and life-threatening disease, so that the propitious financial management is needed to ensure the effectiveness and efficiency of this services. Therefore, it is necessary to do a study of cost of treatment that measures the cost of stroke treatment. The purpose of this study was to describe cost of treatment of stroke patients as BPJS participants in RSUD dr. Mohamad Saleh Probolinggo. This study was partial economic evaluation that aim to describe a cost of an object without comparing with other intervention. It was carried out at RSUD dr. Mohamad Saleh Probolinggo. Sample of this study were stroke patients as BPJS participants in RSUD dr. Mohamad Saleh Probolinggo of 2018 who fulfilled the inclusion and exclusion criteria which is consisted of 40 respondents. The results show that average of direct cost is IDR. 8,278,584. Average of indirect costs is IDR. 974,383. While average of cost of treatment is IDR. 9,252,967. The recommendation is to increase the good recording of nursing actions and do corrective actions. Implementing the monitoring and evaluation to carry out the cost containment.